2017
DOI: 10.1186/s12894-017-0256-9
|View full text |Cite
|
Sign up to set email alerts
|

Alpha1A-adrenoceptor antagonist improves underactive bladder associated with diabetic cystopathy via bladder blood flow in rats

Abstract: Background: Patients with diabetes experience lower urinary tract symptoms. Cystopathy may evolve into underactive bladder (UAB), depending on the degree and duration of the symptoms. In the present study, we aimed to investigate the effects of silodosin, an alpha 1A -adrenoceptor (AR) antagonist, on UAB in a rat model of diabetes mellitus (DM). Methods: Female Sprague-Dawley rats (6 weeks old) were administered streptozotocin (STZ) (50 mg/kg, i.v.) to establish a DM model. One week after STZ administration, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 27 publications
(35 reference statements)
2
21
0
Order By: Relevance
“…However, contrary to our current concept about DCP, some studies have revealed that hyperglycemia does not result in a loss of parasympathetic sensory nerve fibers in the bladder [7]. Therefore, around the world, there has been considerable interest in improving underactive bladder associated with DCP via bladder blood flow [8].…”
Section: Introductionmentioning
confidence: 82%
“…However, contrary to our current concept about DCP, some studies have revealed that hyperglycemia does not result in a loss of parasympathetic sensory nerve fibers in the bladder [7]. Therefore, around the world, there has been considerable interest in improving underactive bladder associated with DCP via bladder blood flow [8].…”
Section: Introductionmentioning
confidence: 82%
“…Additionally, Yonekubo et al . reported that silodosin improved voiding efficiency by increasing BBF in a diabetic cystopathy‐associated DU rat model 19 . Goi et al .…”
Section: Discussionmentioning
confidence: 99%
“…8,9,[16][17][18] Additionally, Yonekubo et al reported that silodosin improved voiding efficiency by increasing BBF in a diabetic cystopathy-associated DU rat model. 19 Goi et al reported that silodosin prevented the decrease in nerve distribution of the bladder and the increase in nerve growth factor expression by improving BBF in an atherosclerosis rat model, and ameliorated detrusor contractile function. 20 Tadalafil has also been reported to improve BBF in not only a BOO rat model, but also a DU rat model induced by diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the majority of studies examining DM complications have focused on the pathogenesis and management of diabetic cystopathy, one of the most common complications of DM (1,2). Diabetic cystopathy is considered to be a manifestation of polyneuropathy, involving sensory and autonomic nerve fibers 1 (3).…”
Section: Introductionmentioning
confidence: 99%